Improving The Ability of Mothers in Stimulation Toodler Development - Sri Endriyani; Eva Susanti (Health Media, 2020)
One of the efforts to maintain and improve mental health in the community, especially children aged toodler, is to optimize the stimulation of growth and development of children aged toodler in order to achieve developmental tasks according to stages and ages. This study aims to see the increase in the ability of parents to stimulate growth and development of Todler-aged children.The design used in this study was "Quasi-experimental pre-post test with control group" with therapeutic intervention group toodler therapy. The population in this study were mothers who had toddler age children with a total sample of 50 respondents. The therapy for this particular group was carried out for 8 weeks. From the results of this study it is known that there is an effect of therapeutic group therapy on mother’s cognitive and psychomotor abilities.